Shared neural signatures of photophobia in migraine and post-traumatic headache: a task-based fMRI study - Rune Häckert Christensen; Haidar Muhsen Al-Khazali; Anna Gudrun Melchior; Messoud Ashina; Håkan Ashina (The Journal of Headache and Pain)
Abstract Background Persistent post-traumatic headache (PTH) and migraine frequently present with photic hypersensitivity that exacerbates headache symptoms. We sought to determine whether persistent PTH is associated with altered brain responses to visual stimuli and to explore shared neural mechanisms of photophobia with migraine. Methods This cross-sectional functional magnetic resonance imaging (fMRI) study included 80 adults with persistent PTH, 261 with migraine, and 143 healthy controls (HCs). All participants underwent visual stimulation using a flickering checkerboard during a 3T fMRI session. Blood oxygen level-dependent (BOLD) responses were examined using whole-brain and region-of-interest (ROI) analyses. All analyses were adjusted for age and sex. Results Whole-brain analysis revealed no significant BOLD differences across the full persistent PTH, migraine, and HC groups. However, participants with persistent PTH who experienced photophobia during the scan (n = 41) showed greater activation in the anterior and midcingulate cortex compared with HCs (P FWE = 0.010). No differences were observed between photophobic participants with persistent PTH and those with migraine who reported an attack during the fMRI session. ROI analyses identified greater activation in the anterior cingulate, midcingulate, and insular cortices in both photophobic participants with persistent PTH and ictal participants with migraine, relative to HCs (all P < 0.05). No significant differences were found between photophobic participants with persistent PTH and ictal participants with migraine. Conclusions Photophobia in persistent PTH is associated with greater activation in cortical regions implicated in pain processing. These patterns parallel those observed during migraine attacks, indicating shared neural mechanisms between the two headache disorders.